2016
DOI: 10.1038/srep37971
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation water productivity is more influenced by agronomic practice factors than by climatic factors in Hexi Corridor, Northwest China

Abstract: Quantifying the influence of driving factors on irrigation water productivity (IWP) is vital for efficient agricultural water use. This study analyzed contributions of agronomic practice and climatic factors to the changes of IWP, based on the data from 1981 to 2012 in Hexi Corridor, Northwest China. Cobb-Douglas production functions were developed by the partial least squares method and contribution rates of the driving factors were calculated. Results showed that IWP and its driving factors increased during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 39 publications
(54 reference statements)
2
39
1
2
Order By: Relevance
“…Although the yield may increase to some extent, the seed quality could not be guaranteed and the corresponding irrigation scheduling would not be acceptable by decision-makers. The results from model (9) showed that the obtained yield was within the bounds of models (7) and (8); therefore, the results of model (7) were reasonable. However, there was only one strategy from model (9) that corresponded to one group value of ET m and EP.…”
Section: The Advantages Of the Proposed Modelmentioning
confidence: 68%
See 2 more Smart Citations
“…Although the yield may increase to some extent, the seed quality could not be guaranteed and the corresponding irrigation scheduling would not be acceptable by decision-makers. The results from model (9) showed that the obtained yield was within the bounds of models (7) and (8); therefore, the results of model (7) were reasonable. However, there was only one strategy from model (9) that corresponded to one group value of ET m and EP.…”
Section: The Advantages Of the Proposed Modelmentioning
confidence: 68%
“…The local climate features typical arid characteristics including low precipitation (50-150 mm/year) and high evaporation (1500-2500 mm/year) [9,33,34]. The seed maize has five growth stages, including establishment, vegetative, flowering, yield-formation, and ripening.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…This has been drawing the attention of researchers for increasing the productivity of onion crop in the region via introducing efficient irrigation water management strategies. Several studies [27][28][29][30] showed that among the different irrigation methods, drip and sprinkler irrigation methods increases the yield of onion and water productivity. However, due to lack of technical knowledge, high labour demand, and poor extension services, these irrigation methods are not well adapted and farmers are distrustful to their acceptance [14].…”
Section: Introductionmentioning
confidence: 99%
“…Irrigated agriculture, the major contributor of agricultural production, faces the challenge of improving irrigation water use efficiency and meanwhile ensuring food security (Li et al, 2016a). The global water consumption for irrigation has been steadily growing over the last 50 years and today it makes 70% of all water consumption (Tian et al, 2016).…”
Section: Introductionmentioning
confidence: 99%